Ethnobotany and exploitation of medicinal plants in the Rhodope Mountains - is there a hazard for Clinopodium dalmaticum? - Irena Mincheva; Michaela Jordanova; Niko Benbassat; Ina Aneva; Ekaterina Kozuharova (Pensoft Publishers, 2019)
The present work summarises preliminary results of an ethnobotanical study in the Rhodope Mountains. The aim was to assess the traditional home use of medicinal plants for herbal tea by local people and to estimate the threats to the Balkan endemic Clinopodium dalmaticum. Semi-structured interviews with local informants from 15 localities in Central and Eastern Rhodope Mountains were performed in 2015 and 2018. As a result, the most used plant species were listed. The major source of plants was recorded as being gathered from the wild. The plants, known with the local names "wild mint" and "white mint", were identified as Clinopodium dalmaticum from dried specimens presented by informants in Central Rhodopes. A frequent collection from wild populations of C. dalmaticum in Central Rhodope Mts. (Smoljan region) was revealed along with just a few cases of cultivation close to the studied sites.